2013
DOI: 10.1017/s136898001300253x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and physical activity level in the prediction of metabolic syndrome in children

Abstract: Objective: To evaluate the effectiveness of anthropometric measures and physical activity level in the prediction of metabolic syndrome (MetS) in children. Design: Cross-sectional study with children from public and private schools. Children underwent an anthropometric assessment, blood pressure measurement and biochemical evaluation of serum for determination of TAG, HDL-cholesterol and glucose. Physical activity level was calculated and number of steps per day obtained using a pedometer for seven consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…They may also herald the presence of cardiovascular risk factors already in childhood as demonstrated in previous studies. [1][2][3] Thus, a more sophisticated approach to assess body composition early in childhood may improve the prediction of cardiometabolic risk. 4 Efforts to obtain detailed information on body composition in children have been impeded by two factors.…”
Section: Introductionmentioning
confidence: 99%
“…They may also herald the presence of cardiovascular risk factors already in childhood as demonstrated in previous studies. [1][2][3] Thus, a more sophisticated approach to assess body composition early in childhood may improve the prediction of cardiometabolic risk. 4 Efforts to obtain detailed information on body composition in children have been impeded by two factors.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, Taylor et al, in their study with 187 Brazilian schoolchildren, also concluded that C‐Index is a less accurate discriminator for abdominal obesity than WC. Since C‐Index was created for use in adult subjects, according to Andaki et al, their ability in young subjects to assess abdominal obesity as an essential component of MetS could be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that high total and central subcutaneous fat mass measures, estimated from skinfold thicknesses, are associated with an adverse cardiovascular risk profile, namely high blood pressure, an unfavorable blood lipids profile and high insulin levels, in late childhood (8)(9)(10)12,34). Another study has shown that an increase in total subcutaneous fat mass from 8 to 18 years old was associated with an increase in total-cholesterol, LDL-cholesterol, and triglycerides levels and a decrease in HDL-cholesterol levels (11).…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
“…We have previously reported in a cross‐sectional study among 6‐year‐old children that both general and abdominal fat mass measures are associated with cardiovascular risk factors, independently of body mass index . Also, previous studies have shown that high total subcutaneous fat mass measured by the sum of skinfold thicknesses is associated with high blood pressure, an unfavorable blood lipids profile, and high glucose and insulin levels in childhood . Currently, it is not known whether, next to rapid weight gain, total and regional subcutaneous fat mass development in infancy is associated with cardiovascular risk factors in later life.…”
Section: Introductionmentioning
confidence: 99%